The “The Analysis of Imperative inThe Bilingual Text Called Aluminum Cylinder AMSCUD with K-valve ProYoke/Din (Output connection)”: “The Analysis of Imperative inThe Bilingual Text Called Aluminum Cylinder AMSCUD with K-valve ProYoke/Din (Output connection)” - Ririn Tasumbey (Universitas Bali Dwipa, 2021)
There are lots definitions of linguistics, such as according to Webster (1981), linguistics is the study of human speech including the units, nature, structure, and modification of language. Wardhaugh (1973) stated that linguistics is the scientific study of language. The two definitions of these linguists clearly explain us that linguistics is basically related to language. In conducting this research the writer collect some sources, which are related to the topic she has chosen. There are two kinds on sources used, primary and secondary sources. The primary source is taken from the bilingual text; the source text and target language. The secondary source consists of facts, and opinion outside the word itself, such as dictionary, internet, encyclopedia, books, etc.